Sustainable Urban Development in Singapore Imagining Walkability in an Urban Concrete Jungle - Liow Li Sa, Melissa; Choon-Yin, Sam (Sustainable Development Goals Series, 2023)
XXIX, 316 p. 18 illus., 17 illus. in color.